Association of baseline and longitudinal plasma retinol-binding protein 4 with all-cause mortality in maintenance hemodialysis patients - Lee, Thung-Lip; Wang, Chao-Ping; Hsuan, Chin-Feng; Hsu, Chia-Chang; Lu, Yung-Chuan; Tang, Wei-Hua; Wei, Ching-Ting; Cheng, Ya-Ai; Chung, Fu-Mei; Lee, Yau-Jiunn; Tsai, I-Ting (Frontiers in Endocrinology, 2025)
IntroductionElevated levels of retinol-binding protein 4 (RBP4) have been linked to conditions including cardiovascular disease, type 2 diabetes, obesity, and insulin resistance. However, the associations between baseline and longitudinal RBP4 levels with all-cause mortality in maintenance hemodialysis patients remain uncertain. The aim of this study was to investigate this issue.MethodsA total of 342 consecutive patients undergoing maintenance hemodialysis at a single hemodialysis center between 2010 and 2022 were assessed. Enzyme-linked immunosorbent assay was used to quantify plasma RBP4 concentrations. Patient outcomes were assessed using Cox regression and Kaplan-Meier analyses.ResultsNon-survivors were associated with significantly lower baseline and longitudinal RBP4 levels compared to the survivors. A trend toward reduced all-cause mortality was found across quartiles of baseline and longitudinal RBP4 levels (p for trend < 0.0001). Multivariate analysis showed that the patients in the lowest quartiles (Quartile 1) of baseline and longitudinal RBP4 levels had hazard ratios of 2.22 (95% CI: 1.16-4.31) and 2.44 (95% CI: 1.30-4.84) for all-cause mortality, respectively, compared to those in the fourth quartile. In contrast to the non-survivors, the survivors had significantly higher plasma RBP4 levels during the 1-year follow-up period compared to the levels at the initiation of hemodialysis (p = 0.001). In addition, a positive association was observed between baseline RBP4 concentration and albumin level, while negative associations were observed between baseline RBP4 concentration and levels of aspartate aminotransferase, high-sensitivity C-reactive protein, and mean corpuscular volume. Structural equation model analysis confirmed the effect of RBP4 on mortality.DiscussionAssociations were identified between low baseline and longitudinal RBP4 plasma concentrations and all-cause mortality in our cohort of Taiwanese maintenance hemodialysis patients.